The Perceptions and Attitudes of Residents Towards Urban Green Spaces in Emilia-Romagna (Italy)—A Case Study - Zhengyang Xu; Teodoro Georgiadis; Letizia Cremonini; Sofia Marini; Stefania Toselli (Land)
Rapid urbanisation has highlighted the importance of urban green spaces (UGS) in promoting environmental sustainability and human wellbeing, yet the gap between urban planning practices and community preferences remains a significant challenge. This study investigated residents’ perceptions and attitudes towards UGS in a neighbourhood of an Italian city (Quartiere Marconi, Imola), focusing on understanding both the strengths and limitations of existing public green spaces from users’ perspectives. Through a comprehensive questionnaire survey of 126 residents, we examined the associations between socio-demographic characteristics and four aspects of UGS utilisation: visiting purposes, barriers to visits, satisfaction levels, and suggestions for improvement. Chi-square tests were conducted to identify significant relationships. The results indicate that life stage, rather than scattered socio-demographic factors, plays a crucial role in shaping UGS perceptions and usage patterns. Particularly, the 31–45 and 46–60 age groups, characterised by family-caring and career responsibilities, showed distinct preferences for social activities, while individual users focused more on nature enjoyment. Although accessibility was generally sufficient, satisfaction levels varied significantly based on living arrangements, with families emphasising facility-related issues and individual users prioritising natural features. These findings suggest that successful UGS planning requires attention to both high-quality natural elements and user-oriented facilities to meet the diverse needs of different life stages. This study represents the preliminary phase of a project, which concerns the redevelopment of the area under study, in order to create a more inclusive and high-quality UGS, taking into account the needs of the resident population.